Analysis of SME (Small and Medium Enterprise) Banking of BRAC Bank Limited - Hossain, Md. Faruk (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.